An Investgation in to Rainfall over Kerala using Satellite Images Analyzed using Discrete Cosine Transform - Rishidas S; Maheswary V AND Sujith Kumar T P (International Journal of Engineering Research & Technology (IJERT), 2015)
Rain, the liquid form of precipitation, plays a significant role in hydrologic cycle. This work is to do rainfall estimation based on satellite images in visible channel using classification techniques. The features of satellite images are taken using the image moments, so that reliable rainfall prediction of the day to be a rainy day or not is made using same day images.